Perbedaan Kegigihan Ditinjau Dari Jenis Mindset Pada Mahasiswa Fakultas Psikologi Universitas Medan Area Angkatan 2019 Yang Menyusun Skripsi - Tesalonika, Miranda Thalita; Saragih*, Adelin Australiati; Lestari Purba, Anggi Tri (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to find out the differences in persistence in terms of the type of mindset in students of the Faculty of Psychology, University of Medan Area Class of 2019 who are compiling thesis. Quantitative research method with different test approach. The sample in the study was 77 2019 students who were taken from the results of screening research data. The persistence scale was prepared using the Likert scale method and the mindset using the Gutmann scale method. Based on the calculation results from the Test Analysis, it is known that there are differences in persistence in terms of student mindset. This result is known by looking at the value or coefficient of difference with the coefficient T = 19,741 with p = 0,000 0.050. Based on these results, it means that the hypothesis proposed which says there is persistence in terms of the student's mindset, is declared accepted. Based on the results of the mean test, it can be concluded that the persistence of the growth mindset is higher with a hypothetical mean value of 120 and an empirical mean of 138.06. the persistence of the fixed mindset is low with a hypothetical mean value of 120 and an empirical mean of 81.24.